2022
DOI: 10.3390/w14050736
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learnt from the Application of MCDA Sorting Methods to Pipe Network Rehabilitation Prioritization

Abstract: Most water distribution networks were built a few decades ago, showing symptoms of deterioration. Additionally, current renewal rates are insufficient to overcome pipe networks’ continuous ageing process. The development of methodologies for assisting the definition of pipe rehabilitation, including which pipes, and when and what financial amounts to allocate to this activity, are of the utmost importance. These methodologies typically have to attend to several points of view, for which multicriteria decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A novel approach to support pipe rehabilitation has been developed to group network segments instead of grouping individual pipes and scheduling rehabilitation in a mediumand long-term perspective. This approach is divided into two main phases: the first is the definition of pipe grouping according to an available budget and contiguity (referred to as rehabilitation units), and the second is the interventions' scheduling overtime according to predefined criteria, defined by Caetano et al [30].…”
Section: Prioritization Of Rehabilitation Units For Interventionsmentioning
confidence: 99%
“…A novel approach to support pipe rehabilitation has been developed to group network segments instead of grouping individual pipes and scheduling rehabilitation in a mediumand long-term perspective. This approach is divided into two main phases: the first is the definition of pipe grouping according to an available budget and contiguity (referred to as rehabilitation units), and the second is the interventions' scheduling overtime according to predefined criteria, defined by Caetano et al [30].…”
Section: Prioritization Of Rehabilitation Units For Interventionsmentioning
confidence: 99%
“…Francisque et al (2014) developed a decision-making tool based on a risk approach and a hybrid genetic algorithm (HGA), named Water main Replacement Risk-based Model (WARRM) to priorities the rehabilitation of drinking water pipes. Other researchers have used machine learning model (Raspati et al, 2022) while several other researchers have applied at least one of the MCDM methods for planning the rehabilitation of WDN (Scholten, Scheidegger, Reichert, Mauer, & Lienert, 2014;Caetano, Carriço, & Covas, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, it is concluded that the knowledge of experts can be as important as the numerical data in the policy making processes of any field in public services, like pipe renovation planning. Caetano et al (2022) prioritized the pipes of a drinking WDN to facilitate modification implementing the MCDM technique. It was attained that this type of planning affects the annual budget for WDN reconstruction.…”
Section: Introductionmentioning
confidence: 99%